2022
DOI: 10.1007/s11695-022-05964-7
|View full text |Cite
|
Sign up to set email alerts
|

Five Year Trends in the Utilization of Robotic Bariatric Surgery Procedures, United States 2015–2019

Abstract: Background: To evaluate the national 5-year utilization trends and outcomes in robotic metabolic and bariatric surgery (MBS).Study design: Retrospective analysis of 2015-2019 MBSAQIP data. Kruskal-Wallis test/Wilcoxon ranksum test and generalized linear models were used to compare continuous/categorical variables. Chi square tests were used to compared robotic versus laparoscopic approaches.Results: The use of robotic MBS increased from 6.2% in 2015 to 13.5% in 2019 (N= 775,258). Robotic MBS patients had margi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Thomas et al performed a similar study with results comparable to Tatarian et al, demonstrating a 1.96-fold increase in the number of robotic bariatric cases performed between 2015 and 2018 [ 14 ]. More recently, Morales-Marroquin et al demonstrated that between 2015 and 2019, there was an increasing trend in robotic surgery that correlated with a decline in laparoscopy [ 15 ]. Although our findings are in line with what was previously reported, our study categorized all the commonly performed MBS procedures separately (SG, RYGB, RBS, and BPD-DS) and included more recent data by incorporating the 2020 PUF in order to see whether there is a difference in the adoption rates between the different procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Thomas et al performed a similar study with results comparable to Tatarian et al, demonstrating a 1.96-fold increase in the number of robotic bariatric cases performed between 2015 and 2018 [ 14 ]. More recently, Morales-Marroquin et al demonstrated that between 2015 and 2019, there was an increasing trend in robotic surgery that correlated with a decline in laparoscopy [ 15 ]. Although our findings are in line with what was previously reported, our study categorized all the commonly performed MBS procedures separately (SG, RYGB, RBS, and BPD-DS) and included more recent data by incorporating the 2020 PUF in order to see whether there is a difference in the adoption rates between the different procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The global adoption of robotic surgery continues to rise in different surgical specialties like colorectal [ 1 3 ], urology [ 4 , 5 ], bariatrics [ 6 8 ], upper gastrointestinal [ 9 11 ] and gynecology [ 12 14 ]. While a large proportion of the robotic systems currently installed are the well-established da Vinci robotic surgical system (Intuitive Surgical Inc, California, USA), various manufacturers have developed and introduced alternative robotic systems.…”
Section: Introductionmentioning
confidence: 99%
“…As an effective treatment [ 2 ], bariatric surgery is performed primarily via a laparoscopic approach, accounting for roughly 90.4% of all bariatric cases [ 3 ]. A slow adoption of robotic-assisted surgery (RAS) has been observed in bariatric surgery [ 3 , 4 ], in contrast to rapid adoption within other specialties (e.g., gynecology and urology) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%